Editorial. Words and silences of architecture (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2015)
The architectural Order, together with the idea of constructive order, declined in every language, in every culture – from Greece to China and beyond – in its universality, in its glory, in its rejection and its tenacious survival, in its conscious use, implied or obliged, therefore, deserves more than just a number of a magazine that wants to talk about architecture, like ours. For this reason, in the meantime, we continue to discuss it in this issue, the second that Ludovico Micara's wise direction opens to wider horizons. With the commitment to return to talk about it again as soon as possible.